Retrospective Comparison of Weight Gain between Olanzapine- and Risperidone-Treated Patients - Rahim, Twana Abdulrahman (Zanco Journal of Medical Sciences (ZJMS), 2010)
Background and objective: Weight gain as a side effect of the second generation antipsychotics have been increasingly noted during therapy; however no studies addressed such a valid clinical concern in Iraq till now. The objective of this study was to determine the weight changes among patients treated with either Olanzap-ine or Risperidone. Methods: A retrospective study was performed by reviewing the charts of 80 patients who have been treated with Olanzapine monotherapy (60 patients) or Risperidone monotherapy (20 patients) through the period of April 2008 to April 2009, compar-ing the baseline weight in kilograms with after one month of therapy weight. Results: Among the 60 patients treated with Olanzapine, 42 (70%) gained weight, 70.37% of males and 69.69% of females treated with Olanzapine gained weight. Among the 20 patients treated with Risperidone, 12 (60%) gained weight, 50% of males and 75% of females treated with Risperidone gained weight. Those treated with Olanzapine, gained 3.96 kg after 30 days of treatment, while the amount of gain was 2.25 kg among those treated with Risperidone after the same period. Olanzapine-treated group gained about 6.21% of their baseline weight which was significantly higher than that of Risperidone-treated group who gained about 2.89% of their baseline weight (P value of 0.03). Females gained more amount of weight than males in both group. Conclusion: Both second generation antipsychotics, Olanzapine and Risperidone, are associated with weight gain. However, Olanzapine appears to have a greater potential in inducing weight gain. Both genders affected nearly equally, though females were victims of more amount of weight gain.